Unraveling amyloid toxicity pathway in NIH3T3 cells by a combined proteomic and 1H‐NMR metabonomic approach12. Issue 6 (25th February 2013) - Vilasi, Annalisa; Vilasi, Silvia; Romano, Rocco; Acernese, Fausto; Barone, Fabrizio; Balestrieri, Maria Luisa; Maritato, Rosa; Irace, Gaetano; Sirangelo, Ivana
Abstract A range of debilitating human diseases is known to be associated with the formation of stable highly organized protein aggregates known as amyloid fibrils. The early prefibrillar aggregates behave as cytotoxic agents and their toxicity appears to result from an intrinsic ability to impair fundamental cellular processes by interacting with cellular membranes, causing oxidative stress and increase in free Ca2+ that lead to apoptotic or necrotic cell death. However, specific signaling pathways that underlie amyloid pathogenicity remain still unclear. This work aimed to clarify cell impairment induced by amyloid aggregated. To this end, we used a combined proteomic and one‐dimensional 1H‐NMR approach on NIH‐3T3 cells exposed to prefibrillar aggregates from the amyloidogenic apomyoglobin mutant W7FW14F. The results indicated that cell exposure to prefibrillar aggregates induces changes of the expression level of proteins and metabolites involved in stress response. The majority of the proteins and metabolites detected are reported to be related to oxidative stress, perturbation of calcium homeostasis, apoptotic and survival pathways, and membrane damage. In conclusion, the combined proteomic and 1H‐NMR metabonomic approach, described in this study, contributes to unveil novel proteins and metabolites that could take part to the general framework of the toxicity induced by amyloid aggregates. These findings offer new insights in therapeutic and diagnostic opportunities. J. Cell. Physiol. 228: 1359–1367, 2013. © 2012 Wiley Periodicals, Inc.